External Influences on Students’ Choice of Clothing in Takoradi Polytechnic - S., Azuah (Journal of Economics and Behavioral Studies, 2014)
Clothing is an important factor in the interpretation of body image which affects the response behaviour of the beholder. A person’s appearance profoundly affects the way he or she is treated by others at home, social gathering, market, job area, office or school. Selecting clothing requires careful considerations. The purpose of the study was to find out external influences on students’ choice of clothing in Takoradi Polytechnic. The research design was descriptive. Questionnaires and focus group discussion guide were used. Departments of Fashion and Accounting participated with respondents chosen through stratified random sampling. Sample consisted of 207 with a total population of 699 students, 77 males and 130 females. Study revealed students dress casually for lectures instead of formally because casual wear could take any form. Male students’ were normally driven internally indicating individuality while female students were mostly externally directed. Both sexes would least choose clothing for warm relationship. The more individuals they were aware of their inner feelings, the more differentiation they exhibited in their choice of clothing. This is contrary to the general perception that students or the youth choice of clothing is socially driven. However, some external factors were also quite significant in students’ choices and should be given close attention if youth clothing are undesirable. This calls for continues education to streamline vital issues that are of significance to academic institutions and the African society as a whole.